2021
DOI: 10.1007/s00586-021-06722-6
|View full text |Cite
|
Sign up to set email alerts
|

Unintended fusion in cervical artificial disk replacement: a prospective study on heterotopic ossification, progression, and clinical outcome, with 5-year follow-up

Abstract: Purpose Heterotopic ossification (HO) may cause unintended fusion in artificial disk replacement (ADR), failing to preserve motion. The reported incidence of HO varies hugely. This study aimed to determine prevalence of HO, progression, predisposing factors to occurrence and to progression, and potential effect on clinical outcomes. Methods Eighty-three patients treated with ADRs for cervical radiculopathy at one or two segments were extracted from a previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, spontaneous fusion occurred in 27% of ADR implants at 5 years of follow-up. 28 In our study with 10 years of follow-up, 34% of the ADR implants had unintended fusion. Spontaneous fusion tends to occur within the first 5 years after surgery, and then the process seems to slow down.…”
Section: Table 3 Pp Analysis Of Baselinementioning
confidence: 51%
“…However, spontaneous fusion occurred in 27% of ADR implants at 5 years of follow-up. 28 In our study with 10 years of follow-up, 34% of the ADR implants had unintended fusion. Spontaneous fusion tends to occur within the first 5 years after surgery, and then the process seems to slow down.…”
Section: Table 3 Pp Analysis Of Baselinementioning
confidence: 51%
“…Male sex is widely recognized as an unfavourable predictor of HO formation after various surgeries such as arthroplasty, 41,42 cervical disc replacement, 43 oncological prostheses implantation, 44 and operations for different trauma, including proximal humerus 45 and acetabulum. 46 In this study, we found that male sex had an adjusted odds ratio (OR) value of 1.64 (95% CI 1.04 to 2.56) compared to female in elbow trauma, which reflects the findings of Cirino et al 45 in proximal humeral fractures (OR 3.57 (95% CI 1.30 to 9.80)).…”
Section: Discussionmentioning
confidence: 99%
“…5). Evidence suggests that HO formation does not compromise patient-reported outcomes [31,32] but radiological studies are lacking. The loss of motion-preservation may lead to increased rates of ASD, as reported with ACDF.…”
Section: Heterotopic Ossification and Fusion After Cervical Disc Tota...mentioning
confidence: 99%